Cash holdings and corporate governance: The effects of premium listing in Brazil - Aviner Augusto Silva Manoel; Marcelo Botelho da Costa Moraes; Marcelo Nagano; Vinicius Amorim Sobreiro (Review of Development Finance, 2018)
Although some studies have analysed the effects of corporate governance practices on cash holdings, this study is the first, to the best of our knowledge, to analyse the effects of a non-mandatory premium listing that was designed to establish a higher standard of governance set by Brazilian public companies. The creation of a domestic and non-mandatory premium listing in 2000 offers a unique opportunity to analyse the relation of its adoption on cash holdings. For this purpose, we used a sample of Brazilian companies between 2001 and 2014. The results indicate, after controlling for endogeneity through the Generalized Method of Moments (GMM) by dynamic panel data, that only firms listed in the New Market (NM), where companies can only issue shares with voting rights, obtained positive significance. Therefore, the issuance of only voting shares reduces agency costs and managerial entrenchment, and consequently reduces the expropriation of the cash holdings, given its vulnerability. In this way, the results obtained in this study contribute to the literature, especially for emerging markets where the use of non-voting shares is common, by pointing out that investors can have greater confidence on cash holdings management in companies where only voting shares are allowed.
Keywords: G31; G34; M40; 650; Working capital management; Emerging markets; Dual-class shares; Cross-listings